Development of SIBAJA Video-Based Learning Media on Tembang Pangkur Material for Junior High School Level - Ratwesti, Glade; Sukoyo, Joko (research, training and philanthropy institution Natural Aceh, 2025)
This research is development research that aims to develop a video-based learning media for tembang macapat pangkur called SIBAJA. The unavailability of learning media causes learning to seem monotonous and causes students to feel bored. Teachers and students of grade VIII at SMP Negeri 34 Semarang need a complete audio-visual learning media and an attractive design to support the learning process of Javanese tembang macapat Pangkur material. The method used in this research is Research and Development. Data collection techniques include observation, interview, and questionnaire techniques. Material experts and media experts carried out product design validation. The validation results from material experts get a percentage value of 95%, and media experts get a percentage value of 90% of the maximum value of 100%. After improving the product prototype based on input and expert suggestions, this video-based tembang macapat pangkur learning media is suitable for grade VIII SMP Negeri 34 Semarang students. This media is expected to be able to overcome existing learning problems and meet the needs of teachers and students so that it can be utilized and utilized as a support for the Javanese language learning process on tembang macapat Pangkur material.